Gangguan fisiologis wereng batang padi coklat akibat pemberian abu terbang batubara - Hafiz Fauzana; F. X. Wagiman; Edhi Martono (Jurnal Entomologi Indonesia, 2014)
Coal fly ash (CFA) can be used as a control agent of brown plant hopper (BPH) Nilaparvata lugens (Hemiptera; Delphacidae). This study was aimed to investigate the physiological disorders in BPH when exposed to CFA. The research was conducted by carrying out tests covering the mortality of BPH, measurement of BPH weight before and after CFA treatment, an analysis of the moisture content in BPH, an analysis of the BPH tissue, and a chemical analysis of BPH. The results of the study showed that the mortality rate of BPH after treatment was 71%. The physiological disorders due to CFA treatment was indicated by a 67.04% weight reduction as opposed to a 6.9% weight increase on the control specimens. The average moisture content of the treated BPH was significantly lower than that of the control specimens. CFA caused a shrinkage of body tissues and an increase in the contents of silica and alumina on BPH.